2016
DOI: 10.1080/15548627.2016.1239676
|View full text |Cite
|
Sign up to set email alerts
|

GFRA1 promotes cisplatin-induced chemoresistance in osteosarcoma by inducing autophagy

Abstract: Recent progress in chemotherapy has significantly increased its efficacy, yet the development of chemoresistance remains a major drawback. In this study, we show that GFRA1/GFRa1 (GDNF family receptor a 1), contributes to cisplatin-induced chemoresistance by regulating autophagy in osteosarcoma. We demonstrate that cisplatin treatment induced GFRA1 expression in human osteosarcoma cells. Induction of GFRA1 expression reduced cisplatin-induced apoptotic cell death and it significantly increased osteosarcoma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 60 publications
2
132
1
Order By: Relevance
“…In response to adverse stress, such as nutrient starvation, autophagy may be triggered for the degradation of unnecessary molecules, serving as a potential survival mechanism to maintain intercellular homeostasis, regulate the immune response and remodel development (32,33). Studies suggest that autophagy induction is a mechanism of chemoresistance (34,35). On the contrary, numerous anticancer agents, such as resveratrol, induce autophagic cell death, indicating that autophagy may be a vital mechanism for anticancer therapy (36).…”
Section: Discussionmentioning
confidence: 99%
“…In response to adverse stress, such as nutrient starvation, autophagy may be triggered for the degradation of unnecessary molecules, serving as a potential survival mechanism to maintain intercellular homeostasis, regulate the immune response and remodel development (32,33). Studies suggest that autophagy induction is a mechanism of chemoresistance (34,35). On the contrary, numerous anticancer agents, such as resveratrol, induce autophagic cell death, indicating that autophagy may be a vital mechanism for anticancer therapy (36).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has been claimed to play a paradoxical role in controlling cell death and survival in response to various stimuli [27]. Previous studies have reported that induction of autophagy could promote cisplatin-induced chemoresistance in osteosarcoma [28]. To investigate the role of CDDPor PLB-induced autophagy, the inhibitor 3-methyladenine (3-MA, inhibitor of early autophagy/LC3-II accumulation) was used to pretreat TSCC cells.…”
Section: Plumbagin Enhanced the Proapoptosis Effect Of Cisplatin In Tmentioning
confidence: 99%
“…The second BC group is composed by highly expressed genes including SMAD2, SMAD4, TCF12, ELP2, ATG2B, PIGN, MBP, NCBP3 and PIK3C3, which enrich pathways of cell cycle, cell metabolism regulation, TGF-beta signaling, PI3K cascade, autophagy, immune responses and mRNA production regulation. The third BC group is enriched by a large number of pseudo genes and the protein coding genes in this group enrich the translation regulation and viral infection, in which genes TMA7, DEXI and EIF3CL have been previously reported as related to cisplatin and fluorouracil resistance in bladder and gastric cancer (30, 31). In addition, the four BCs group are also enriched by two different groups of ribosome proteins, which are related to translational control and elongation of peptides.…”
Section: Resultsmentioning
confidence: 99%